The anxious society’s fertility problem: The promoting effect of physical exercise on mental health—An empirical analysis using CGSS data - Jincao Zhai; Dingwu Liu; Mingze Gao; Chunli Han (PLoS ONE, 2026)
The declining willingness to have children is significantly influenced by underlying psychological constraints that cannot be ignored. Providing psychological health support and interventions for the reproductive-age population is crucial for enhancing fertility intentions. Based on data from the 2021 China General Social Survey, this research explores the association between the psychological benefits of physical exercise on individuals’ willingness to bear children. The results indicate a positive correlation between engagement in physical exercise and individual fertility intentions. Specifically, a one-unit higher in level of physical exercise is associated with a 0.099-unit higher level of fertility willingness. Mechanistically, participation in physical exercise is associated with psychological well-being ( β = 0.0133, P < 0.001) and social engagement( β = 0.011, P < 0.001),these factors are, in turn, associated with higher fertility intentions. Heterogeneity analysis reveals that the positive association between physical exercise and fertility intentions is more pronounced among single individuals with higher educational attainment and income levels (β = 0.092, β = 0.109, β = 0.095; P < 0.001), suggesting potential implications for addressing the “fertility-income paradox.”.